AN ANALYSIS OF JOKOWI’S POLICY IN REFUSING THE RETURN OF FORMER ISIS FOREIGN TERRORIST FIGHTERS INDONESIAN CITIZENS - Irfan Amir (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri Bone, 2020)
Industry 4.0 which is supported by the concept of the internet of think has influenced the pattern of indoctrination of radical-terrorism groups. Based on the results of the study, after the declaration until the collapse of the Islamic State of Iran and Syria (ISIS) there were at least 689 foreign terrorist fighters who came from Indonesia and hoped to be repatriated to the country. However, because of security considerations, President Joko Widodo firmly refused. To address this issue, the author conducts normative-empirical legal research using library research methods. The results showed that Indonesian citizens involved in organized international crimes such as ISIS can be banned from returning to Indonesia on a legal basis using Article 98 Paragraph 1 of Law No. 6 of 2011 concerning Immigration and Article 263 Paragraph 2 letter (a) Government Regulation No. 21 of 2013 concerning Regulations for Implementing the Immigration Law. Besides, terrorist sleep cells of ISIS in the country can at any time carry out suicide bomb attacks as a signal given by their group. As an ideological network, these terrorism sleep cells are clandestine and begin to involve women and children as suicide bombers.Keywords: Foreign Terrorist Fighter; Terrorism; ISIS.